PREZENTAREA SINTETICĂ A STRATEGIEI DE DEZVOLTARE PE TERMEN SCURT ŞI MEDIU A MUNICIPIULUI BLAJ (PANGEEA, 2025)
ABSTRACT: Brief presentation strategy development short and medium term of the city Blaj. With the entrance of Romania in the European Community, the administration of the city, established a strategy for economic and social revival, which provides modernization of old infrastructure, landscaping and urban buildings in the historic center, creating green spaces for walking, attracting local and foreign investment lead to a real industrial progress, so "Little Rome" have a future harmonious and balanced development.